Intrauterine death rate in gastroschisis following the introduction of an antenatal surveillance program: Retrospective observational study. Issue 3 (6th February 2017) - Perry, Helen; Healy, Costa; Wellesley, Diana; Hall, Nigel J.; Drewett, Melanie; Burge, David M.; Howe, David T.
Abstract: Aim: To investigate whether an antenatal surveillance protocol including ultrasound and cardiotocograph monitoring reduces intrauterine death (IUD) in cases of gastroschisis. Secondary outcomes included neonatal death rate, mode of delivery and rate of intervention before planned time of delivery. Methods: This was a retrospective observational study of all women with antenatally diagnosed gastroschisis who were managed according to the surveillance program between 2002 and 2015 in a tertiary fetal medicine and pediatric surgical center covering the Wessex region of England. We reviewed and analyzed data from the Wessex Antenatally Detected Anomalies (WANDA) database as well as prospectively managed maternity, ultrasound and neonatal databases over the given time period. Case notes were reviewed when delivery was expedited. Results: The IUD rate was 2.2%, a 58% reduction since the introduction of the surveillance protocol. Delivery was expedited in 35.4% of cases, and in 86% of these, delivery was by cesarean section. In women being induced as planned at 38 weeks, the vaginal delivery rate was 88%, and for those in spontaneous labor before 38 weeks it was 75%. Conclusions: An antenatal surveillance program appears to reduce the IUD in gastroschisis. In one‐third of cases, delivery was indicated before the planned date of delivery. When expedited delivery was indicated, the chance of cesarean section was high.